Effect of moringa leaf consumption on milk quantity in breastfeeding mothers: A Systematic Review - Sardini; Indryani; Hasnidar (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction: Moringa (Moringa oleifera) leaves are rich in nutrients and phytochemicals that may enhance lactation performance. Breastfeeding mothers often experience inadequate milk production, and moringa supplementation has been explored as a potential natural galactagogue. Methods: This systematic review aimed to analyze the effects of moringa leaf consumption on breast milk quantity in lactating mothers. A comprehensive search was conducted using databases such as PubMed, Scopus, and Google Scholar for studies published between 2015 and 2025. Inclusion criteria encompassed randomized controlled trials and observational studies evaluating moringa leaf preparations (powder, extract, or capsules) compared with placebo or standard care. Data extraction focused on milk volume, lactation duration, and maternal nutritional outcomes. Results: Across the included studies, supplementation with moringa leaves consistently increased milk production. Most trials reported a significant increase in milk volume during the first 2 weeks postpartum compared with control groups (p < 0.05). Phytochemical components, such as flavonoids and saponins, in moringa are believed to stimulate prolactin secretion and enhance maternal nutrition. However, variations in dosage, preparation form, and study design led to moderate heterogeneity across studies. Conclusion: Moringa leaf consumption significantly enhances breast milk quantity among lactating mothers. Its use as a natural galactagogue holds promise in improving breastfeeding success and maternal nutrition, particularly in low-resource settings. Moringa leaf supplements can be recommended as a natural galactagogue for breastfeeding mothers, in conjunction with a balanced diet and adequate hydration, to support milk production and infant health.